2023
DOI: 10.1021/acs.energyfuels.2c04377
|View full text |Cite
|
Sign up to set email alerts
|

Highly Dispersed Core–Shell Ni@NiO Nanoparticles Embedded on Carbon–Nitrogen Nanotubes as Efficient Electrocatalysts for Enhancing Urea Oxidation Reaction

Abstract: Wastewater treatment and energy production are important fields of research to meet the current requirements of sustainable energy development and wastewater restoration. The urea oxidation reaction (UOR) can be used for simultaneous environmental remediation and energy production on a priority basis. Nickel−nickel oxide (Ni@NiO) core−shell NPs on carbon−nitrogen nanotubes (CNNTBs) have been synthesized as electrocatalysts by using a simple and easy aerial annealing method. Morphological analysis by high resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…During the anodic potential sweep, the in situ converted metal oxyhydroxide, MOOH (M = Ni, Co, Mn), is the active species for the UOR. Ni based catalysts, like Ni MOF, 85 mesoporous Ni−P, 86 Ni 2 P, 87 NiO, 88,89 Ni@NiO nanoparticles, 90 alloyed Ni nanoparticles like Ni−Rh, 91 Ni−Co, 92 and Ni−Mn, 93 Ni sulfide, 94 Ni based bimetallic oxide/hydroxides such as NiMoO 4 , 95,96 NiCo 2 O 4 , 97 Ni 0.9 Fe 0.1 O x , 98 Cu:α-Ni(OH) 2 , 99 and NiMn−OH, 100 NiCo layered double hydroxide, 101 and Ni based heterostructures like NiCoP/MoS 2 , 102 were employed for the UOR. Zhang et al 81 reported NiMo nanotubes as a bifunctional catalyst (Figure 4A 82 for the overall urea assisted water splitting where only a cell voltage of 1.45 V is required to deliver a 20 mA cm −2 current density in 1 M KOH with 0.33 M urea as well as long-term cell stability for 20 h. DFT calculation predicted that the interface between Ni 3 S 2 and MoS 2 decreases the Gibbs free energy for the UOR.…”
Section: Other Substrate Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…During the anodic potential sweep, the in situ converted metal oxyhydroxide, MOOH (M = Ni, Co, Mn), is the active species for the UOR. Ni based catalysts, like Ni MOF, 85 mesoporous Ni−P, 86 Ni 2 P, 87 NiO, 88,89 Ni@NiO nanoparticles, 90 alloyed Ni nanoparticles like Ni−Rh, 91 Ni−Co, 92 and Ni−Mn, 93 Ni sulfide, 94 Ni based bimetallic oxide/hydroxides such as NiMoO 4 , 95,96 NiCo 2 O 4 , 97 Ni 0.9 Fe 0.1 O x , 98 Cu:α-Ni(OH) 2 , 99 and NiMn−OH, 100 NiCo layered double hydroxide, 101 and Ni based heterostructures like NiCoP/MoS 2 , 102 were employed for the UOR. Zhang et al 81 reported NiMo nanotubes as a bifunctional catalyst (Figure 4A 82 for the overall urea assisted water splitting where only a cell voltage of 1.45 V is required to deliver a 20 mA cm −2 current density in 1 M KOH with 0.33 M urea as well as long-term cell stability for 20 h. DFT calculation predicted that the interface between Ni 3 S 2 and MoS 2 decreases the Gibbs free energy for the UOR.…”
Section: Other Substrate Oxidationmentioning
confidence: 99%
“…During the anodic potential sweep, the in situ converted metal oxyhydroxide, MOOH (M = Ni, Co, Mn), is the active species for the UOR. Ni based catalysts, like Ni MOF, mesoporous Ni–P, Ni 2 P, NiO, , Ni@NiO nanoparticles, alloyed Ni nanoparticles like Ni–Rh, Ni–Co, and Ni–Mn, Ni sulfide, Ni based bimetallic oxide/hydroxides such as NiMoO 4 , , NiCo 2 O 4 , Ni 0.9 Fe 0.1 O x , Cu:α-Ni­(OH) 2 , and NiMn–OH, NiCo layered double hydroxide, and Ni based heterostructures like NiCoP/MoS 2 , were employed for the UOR. Zhang et al reported NiMo nanotubes as a bifunctional catalyst (Figure A–D) to catalyze the HER and UOR in alkaline electrolyte.…”
Section: Hybrid Water Electrolysismentioning
confidence: 99%
“…Herein, the urea molecules with electron-donating amino groups and electron-withdrawing carbonyl groups can be selectively adsorbed on NNC via. Ni/ NiOO-carbonyl group as an intermediate step, 5,[26][27][28][29] followed by the corresponding nucleophilic OH − attack. As a result, cleavage of the C-N bond became more favourable, and UOR could proceed at a lower potential.…”
Section: Effect Of Koh Concentrationmentioning
confidence: 99%
“…To conrm CO 2 as the by-product, we performed the precipitation test using CaCO 3 aer the i-t stability test. 30 CaCO 3 reacts with dilute HCl, evolving CO 2 molecules and forms CaO (i.e., lime). CaO easily reacts with electrolyte solution and forms a white ppt of CaCO 3 .…”
Section: Aer Electrolysis Product Analysis Testmentioning
confidence: 99%
“…Methanol is a typical alcohol, which can be electrochemically oxidized into CO 2 . Urea is a representative and simple amine, which can be oxidized to CO 2 and N 2 at the anode with H 2 forming at the cathode in a combined system. In addition, some inorganic reactions can also be used as the institute of OER to combine with HER for energy effective H 2 production. NO is a typical harmful pollutant, which can be oxidized into nitrate in the combined systems with a potential of ∼1.07 V .…”
Section: Her Coupled With Electrochemical Oxidation Reactionsmentioning
confidence: 99%